Blue light promotes conjunctival epithelial-mesenchymal transition and collagen deposition through ITGB4 - Qianjie Yang; Kuangqi Chen; Siyi Chen; Yinhao Wang; Yutong Xia; Jinbo Chen; Ye Shen (Ecotoxicology and Environmental Safety)
The increasing prevalence of LED technology heightened blue light (BL) exposure, raising concerns about its long-term effects on ocular health. This study investigated the transcriptomic response of conjunctiva to BL exposure, highlighting potential biomarkers for conjunctival injury. We exposed human conjunctival epithelial cells and C57BL/6 mice to BL to establish in vitro and in vivo models and identified the responsive genes in mice’s conjunctiva to BL exposure by RNA sequencing transcriptome analysis. Western blotting, wound healing assays, transwell assay, and phalloidin staining assessed phenotypes of epithelial-mesenchymal transition (EMT). BL disrupted cell conjunction and regulated EMT-related proteins. RNA sequencing analysis revealed upregulation of ITGB4 and enrichment of cell migration and adhesion pathways. Reactive oxygen species-mediated damage caused by BL upregulated ITGB4 expression, promoting cell migration and EMT through the extracellular signal-regulated kinase /Snail pathway.